2011
DOI: 10.1002/dmrr.1162
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus, other medical conditions and pancreatic cancer: a case‐control study

Abstract: Diabetes is associated with heightened risk of pancreatic cancer. The association is significant for diabetes diagnosed up to 10 years before pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Observational studies in humans have demonstrated the existence of relationships between several medical conditions, including cholecystitis [52], cholecystectomy [53], HBV infection [54] and ulcer gastrectomy [19], and an increased risk of pancreatic adenocarcinoma, but these findings have been somewhat contradictory. In our study, we observed a significant positive linear association between the risk of pancreatic adenocarcinoma and cholelithiasis (OR = 5.453).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Observational studies in humans have demonstrated the existence of relationships between several medical conditions, including cholecystitis [52], cholecystectomy [53], HBV infection [54] and ulcer gastrectomy [19], and an increased risk of pancreatic adenocarcinoma, but these findings have been somewhat contradictory. In our study, we observed a significant positive linear association between the risk of pancreatic adenocarcinoma and cholelithiasis (OR = 5.453).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, accumulating evidence has identified long-standing, preexisting chronic pancreatitis, a rare inflammatory condition, as a strong risk factor for pancreatic cancer [12,19,45,46]. Case-control studies have estimated the increased risk of pancreatic cancer for patients with chronic pancreatitis to range from 2 to 16% [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, at least 13 epidemiologic studies have investigated the associations of cholecystectomy and/or gallstones with pancreatic cancer risk. The results obtained from these studies are overall conflicting (Lin and Kessler, 1981; Ekbom et al , 1996; Gullo et al , 1996; Chow et al , 1999; Coughlin et al , 2000; Silverman, 2001; Talamini et al , 2001; Ye et al , 2001; Lin et al , 2002; Schernhammer et al , 2002; Stolzenberg-Solomon et al , 2002; Hassan et al , 2007; Lipworth et al , 2011). Significantly increased risk associated with cholecystectomy and/or gallstones was observed in one case-control study (Silverman, 2001) and four cohort studies (Ekbom et al , 1996; Chow et al , 1999; Coughlin et al , 2000; Lin et al , 2002).…”
mentioning
confidence: 99%
“…Some epidemiological studies have excluded the possibility that long-standing DM is a risk factor for PC [96][97][98][99][100][101][102][103][104][105][106][107][108] , whereas others have found the otherwise [109][110][111][112][113][114][115][116] .…”
Section: Diabetes Mellitus (Dm)mentioning
confidence: 99%